1990
DOI: 10.1091/mbc.1.10.747
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic signaling pathways of growth factors can be distinguished by the involvement of pertussis toxin-sensitive guanosine triphosphate-binding protein and of protein kinase C.

Abstract: We have examined the possible involvements of pertussis toxin (PT)-sensitive guanosine triphosphate (GTP)-binding protein (Gp) So far, two major signal transduction pathways have been shown to be involved in cell growth stimulation: 1) protein-tyrosine phosphorylation, and 2) breakdown of phosphatidylinositol-4,5-bisphosphate (PIP2) into inositol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 58 publications
(49 reference statements)
3
6
0
Order By: Relevance
“…The dose-effect relationship of each agonist for the stimula tion of PI turnover was predetermined. The optimal concentrations used in the present study are consistent with those reported in the literature [7][8][9][10][11][12][13][14][15][16][17][18]. For the agonists with negative responses, the empirical con centrations from the study of other cell types were cho sen to elicit DNA synthesis [10, 12, 13, [16][17][18], The incubation was terminated by removing the labeling solution and rapidly washing with ice-cold Puck's solu tion, followed by adding 1.5 ml 15% trichloroacetic acid (TCA) to each well.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The dose-effect relationship of each agonist for the stimula tion of PI turnover was predetermined. The optimal concentrations used in the present study are consistent with those reported in the literature [7][8][9][10][11][12][13][14][15][16][17][18]. For the agonists with negative responses, the empirical con centrations from the study of other cell types were cho sen to elicit DNA synthesis [10, 12, 13, [16][17][18], The incubation was terminated by removing the labeling solution and rapidly washing with ice-cold Puck's solu tion, followed by adding 1.5 ml 15% trichloroacetic acid (TCA) to each well.…”
Section: Introductionsupporting
confidence: 86%
“…The optimal concentrations used in the present study are consistent with those reported in the literature [7][8][9][10][11][12][13][14][15][16][17][18]. For the agonists with negative responses, the empirical con centrations from the study of other cell types were cho sen to elicit DNA synthesis [10, 12, 13, [16][17][18], The incubation was terminated by removing the labeling solution and rapidly washing with ice-cold Puck's solu tion, followed by adding 1.5 ml 15% trichloroacetic acid (TCA) to each well. The extract of water-soluble inositol phosphates was neutralized and analyzed by high-performance liquid chromatography, as previous ly reported [19], Because inositol trisphosphatc se quentially converts to inositol bisphosphate and inosi tol monophosphate (IP) during the 30-min period of stimulation and because lithium inhibits IP degrada tion, the majority of inositol phosphates in the pres ence of LiCl is IP [6,20].…”
Section: Introductionsupporting
confidence: 86%
“…2-4) suggest that the action of TGF-␤ to stimulate proliferation of Swiss 3T3 and Balb 3T3 cells is unrelated to that of PDGF-AA/-BB, because these mitogens clearly induced the activation of MAP kinases and c-fos gene expression soon after binding to their receptors. The mitogenic potential of TGF-␤1 was not inhibited by the depletion of protein kinase C in Balb 3T3 and Swiss 3T3 cells, which were pretreated with 200 ng/ml of phorbol 12-myristate 13-acetate for 24 h (data not shown), would also support the above conclusion; the capacity of PDGF-AA/-BB to reinitiate DNA synthesis was reduced to ϳ50% in such phorbol 12-my- ristate 13-acetate-pretreated cells compared with the untreated native cells (45). However, we cannot exclude the possibility that TGF-␤1 induces the production of a novel growth factor, which acts as a direct mitogen in fibroblasts through a MAP kinase-/protein kinase C-independent mechanism.…”
Section: Tgf-␤1 Inhibits the Egf-stimulated Proliferation Of Mouse Kementioning
confidence: 72%
“…Cells were cultured in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum. For experimental use, confluent cell cultures in Dulbecco's modified Eagle's medium containing 10% fetal calf serum were rendered quiescent by incubation for 40ϳ48 h in serum-free medium (Dulbecco's modified Eagle's medium containing 2 mg/ml of bovine serum albumin (Boehringer Mannheim), 1 g/ml of insulin, 2 g/ml of transferrin, 20 nM Na 2 SeO 3 , and 10 mM Hepes, pH 7.4), and then growth factors were added (44,45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation